1997
DOI: 10.1074/jbc.272.28.17425
|View full text |Cite
|
Sign up to set email alerts
|

Erythromycin Resistance Peptides Selected from Random Peptide Libraries

Abstract: It was assumed for a long time that the ribosome is indifferent to the sequence of the polypeptide it is synthesizing. New evidence, however, indicates that nascent or newly synthesized polypeptides can affect functions of the ribosome in cis. In a number of cases, the newly translated peptide exerts its effect on translation while still being located within the ribosome. For example, short nascent peptides regulate stalling of the ribosome on mRNA, which is required for inducing the expression of chlorampheni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
93
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(100 citation statements)
references
References 27 publications
(34 reference statements)
7
93
0
Order By: Relevance
“…Moreover, the same study showed that alterations in the size of the peptide possess a strong effect on the resistance levels conferred, suggesting that the Leu residue plays a key role in the dissociation of erythromycin. This finding may be in accordance with the high consensus of previously studied E-peptides selected using erythromycin, which usually presents at least one Leu at position 3 (Tenson et al, 1997). However, this E-peptide model of action cannot be extended to all macrolides.…”
Section: Resistance Mediated By Short Peptidessupporting
confidence: 77%
See 1 more Smart Citation
“…Moreover, the same study showed that alterations in the size of the peptide possess a strong effect on the resistance levels conferred, suggesting that the Leu residue plays a key role in the dissociation of erythromycin. This finding may be in accordance with the high consensus of previously studied E-peptides selected using erythromycin, which usually presents at least one Leu at position 3 (Tenson et al, 1997). However, this E-peptide model of action cannot be extended to all macrolides.…”
Section: Resistance Mediated By Short Peptidessupporting
confidence: 77%
“…Further studies using random peptide libraries have shown a variety of synthetic short peptides of between three and six amino acids able to produce macrolide resistance as well as the inability of these peptides to affect the MIC of erythromycin when included in longer amino acid sequences (Tenson et al, 1997). However, the Shine-Dalgarno region is located in a hairpin at position 1198-1247, being difficult to access by RNA-polymerases (Dam et al, 1996) and probably being unexpressed in normal conditions.…”
Section: Resistance Mediated By Short Peptidesmentioning
confidence: 99%
“…24. A mRNA transcript with the sequence GGGAAUUCGGGCCCUU-GUUAACAAUUAAGGAGGUAUACUAUGAAUGCAAUA-AAUAACUGCAG(A) 21 (25) was prepared by in vitro transcription and purified according to ref. 26.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, macrolide binding seems to be involved in cellular processes. Thus, stalling by specific nascent peptides, a cellular mechanism used for regulation of expression of several bacterial and eukaryotic genes, is sensitive to signals connected with macrolide binding (73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83).…”
Section: Figurementioning
confidence: 99%